Scleromalacia perforans after retinal detachment surgery. - Angela Nurini Agni, Angela Nurini Agni (Universitas Gadjah Mada, 1997)
A 37 year old man suffering from scleromalacia perforans after retinal detachment surgery has been reported. The background whether this patient was suffering from autoimmune disorder or other systemic disease was not determined because of a lack of supporting examination to detect this condition. He underwent free sclera! buckle and scleral grafting followed by a combination of steroid and NSAID. The scleral graft remains stable; however, scleral thinning has been progressively occurring. All of ocular surgery must be accurately prepared. Identification of the risk of systemic disease must be taken, especially the autoimmune disorder. Evidences on the correlation of autoimmune disorder with scleritis after ocular surgery were known well. In conclusion, an accurate and complete information was needed for the patient in order to understand the real condition.Key words : Scleromalacia perforans - autoimmune disorder - graft - retinal ablation